BLIND JUSTICE: AN ANALYSIS OF THE IMPACT OF THE SYMBOLIC LADY JUSTICE IN ADJUDICATION (The Pretoria Student Law Review, 2021)
This article serves as an analysis of the depiction of the neutrality and objectivity of judges through the image of Lady Justice. I will investigate whether this depiction is relevant under the current constitutional dispensation, bearing in mind a value-orientated approach to law. Firstly, I will discuss the historical development of the image of Lady Justice with regards to adjudication. Secondly, I will analyse the relevance of Lady Justice in a post-apartheid South African context. Thirdly, I will provide a discussion on the postapartheid contextual meaning of reconciliation and the onus of a value-orientated approach to adjudication that the Constitution has placed on the courts.
Keywords: neutrality; objectivity; judges; Lady Justice; constitutional dispensation; value-orientated approach; historical development